2012
DOI: 10.1128/aem.00027-12
|View full text |Cite|
|
Sign up to set email alerts
|

Removal and Transfer of Viruses on Food Contact Surfaces by Cleaning Cloths

Abstract: ABSTRACTContamination of food contact surfaces with pathogens is considered an important vehicle for the indirect transmission of food-borne diseases. Five different cleaning cloths were assessed for the ability to remove viruses from food contact surfaces (stainless steel surface and nonporous solid surface) and to transfer viruses back to these surfaces. Cleaning cloths evaluated include two different cellulose/cotton cloths, one microfiber cloth, one nonwoven cloth, and one … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
27
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 51 publications
3
27
0
Order By: Relevance
“…Two studies published in 2012 found that norovirus (human and MNV1 strains) could be substantially reduced on hard surfaces after wiping from one to six times using a range of inocula and material wipes (121,149). This supports the increasingly popular premise that physical removal could challenge routine use of disinfectants for controlling surface microbes (163,164) (Fig.…”
Section: Benefits Of Physically Removing Soilmentioning
confidence: 70%
See 1 more Smart Citation
“…Two studies published in 2012 found that norovirus (human and MNV1 strains) could be substantially reduced on hard surfaces after wiping from one to six times using a range of inocula and material wipes (121,149). This supports the increasingly popular premise that physical removal could challenge routine use of disinfectants for controlling surface microbes (163,164) (Fig.…”
Section: Benefits Of Physically Removing Soilmentioning
confidence: 70%
“…Poor choice of cleaning methods or products or inadequate maintenance of equipment will result in environmental contamination of the very surfaces that need attention. There are numerous examples of cleaning cloths, including those made of microfiber, that merely distribute organisms across surfaces instead of removing them (26,120,142,(147)(148)(149). Enterococci, including VRE, seem to be particularly difficult to eliminate from contaminated cloths (51,147,148).…”
Section: Contamination Of Cleaning Equipment and Liquidsmentioning
confidence: 99%
“…There are increasing reports that suggest physical, rather than biocidal, removal of bioburden is key to the cleaning process [50][51][52][53][54][55][56][57][58]. This is not necessarily due to the fact that surface soil is known to impede microbiocidal activity of a disinfectant [59].…”
Section: The Wiping Effectmentioning
confidence: 99%
“…For influenza virus, chlorine, but also other cleaning agents such as vinegar and quaternary ammonium, is an effective disinfectant (5,29,30). Not only the disinfectant used but also the wiping cloth affects decontamination efficacies and cross-contamination by wiping (33)(34)(35). Gibson et al (34) showed the effect of the type of cloth on the removal of hNoV surrogates from surfaces and their transfer to surfaces, and especially, the transfer to surfaces by wiping with contaminated wipes was greatly affected by the type of cloth, with cotton terry bar towels cross-contaminating surfaces to the greatest extent and microfiber cloth to the least.…”
mentioning
confidence: 99%